Sistem Pemetaan Parkir Menggunakan Teknik Image Processing - Nico Fransisco Utomo; B Budiana; Adlian Jefiza; Fitriyanti Nakul (Journal of Applied Electrical Engineering, 2023)
The large number of people who use private vehicles has an impact on increasing people's need for parking areas, including in residential apartments. Limitations to getting information on the availability of parking slots result in difficulties for drivers finding available parking locations. This study aims to develop an effective parking slot mapping system for apartment managers and users using the configuration of image processing and MySQL servers. System design works to process vehicle plates recognized on camera using segmentation and analysis image processing. Data processing uses a visual studio tool as an interface that is connected to MySQL as a database server and activates the visualization of slots and parking locations through the Blynk apps. The results show that the system can read detected vehicle plates and send notifications to Blynk apps to inform the slot status and available parking locations. System testing was carried out for any variations of distance and camera angle positions to determine the standard parameters for a good operating system